2006
DOI: 10.1007/s00221-006-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials modulation during direct current cortical polarization

Abstract: Transcranial direct current stimulation (tDCS) at low intensity induces changes in cortical excitability that persist after polarization ends. The effects of anodal and cathodal polarization remain controversial. We studied changes in visual evoked potentials (VEPs) during and after anodal and cathodal tDCS by applying, in healthy volunteers, 1 mA polarization through surface electrodes placed over the occipital scalp (polarizing) and over the anterior or posterior neck-base (reference). We compared tDCS appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 21 publications
6
141
2
1
Order By: Relevance
“…Therefore, the cathodal stimulation was completely ineffective from a behavioral perspective. The absence of a cathodal effect has also been reported in previous studies (Antal et al, 2004d;Fertonani et al, 2010;Kraft et al, 2010), although several papers have reported either inhibitory (Antal et al, 2001(Antal et al, , 2003a(Antal et al, ,b, 2004a or facilitatory (Antal et al, 2004c;Accornero et al, 2007) effects. This discrepancy is probably due to several factors, such as the different experimental tasks (e.g., patternreversal checkerboard vs sinusoidal luminance gratings) and the differences in stimulation parameters (e.g., intensity, duration, electrode size, and the location and direction of the current flow) (Nitsche et al, 2008).…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, the cathodal stimulation was completely ineffective from a behavioral perspective. The absence of a cathodal effect has also been reported in previous studies (Antal et al, 2004d;Fertonani et al, 2010;Kraft et al, 2010), although several papers have reported either inhibitory (Antal et al, 2001(Antal et al, , 2003a(Antal et al, ,b, 2004a or facilitatory (Antal et al, 2004c;Accornero et al, 2007) effects. This discrepancy is probably due to several factors, such as the different experimental tasks (e.g., patternreversal checkerboard vs sinusoidal luminance gratings) and the differences in stimulation parameters (e.g., intensity, duration, electrode size, and the location and direction of the current flow) (Nitsche et al, 2008).…”
Section: Discussionsupporting
confidence: 60%
“…Such response characteristics respectively follow the known contrast response functions of the parvocellular and magnocellular pathways to sinusoidal luminance gratings (Benardete et al 1992;Benardete and Kaplan 1997a,b;Derrington and Lennie 1984;Merigan and Eskin 1986;Merigan and Maunsell 1993;Tootell et al 1988). Additionally, both C1 and P1 components have been shown to be pharmacologically separable in the cat visual cortex (e.g., Arakawa et al 1993;Zemon et al 1980) and are differentially modulated by cathodal or anodal stimulation in transcranial direct current stimulation (tDCS) paradigms with human participants (Accornero et al 2007;Antal et al 2004). The pharmacological separability of the C1 and P1 VEP components in cats and differential modulation of the same components in humans using tDCS would both be expected if each component were generated by different neural populations.…”
mentioning
confidence: 57%
“…Several studies showed that tDCS might modulate cortical excitability in the human motor cortex (Boggio, Castro, et al, 2006;Boggio et al, 2007;Boros, Poreisz, Münchau, Paulus, & Nitsche, 2008), visual cortex (Accornero, Li Voti, La Riccia, & Gregori, 2007;Antal et al, 2004), and parietal cortex (Sparing et al, 2009;Stone & Tesche, 2009) and also could have clinical implications (Brunoni et al, 2012). In addition to motor and visual learning tasks, tDCS has been effectively used in memory studies, especially working memory (Boggio, Ferrucci, et al, 2006;Fregni et al, 2005;Jo et al, 2009), episodic memory, and declarative memory (Javadi & Walsh, 2012;Marshall, Mölle, Hallschmid, & Born, 2004).…”
Section: Introductionmentioning
confidence: 99%